From less to maximally invasiveness in cervical spine surgery: A "nightmare" case who deserve consideration. (2015) - Visocchi, M.; Conforti, G.; Roselli, R.; La Rocca, G.; Spallone, A.
Highlights: The fragility of soft and hard articulation structures in AR cervical spine can play a role in destabilizing the construct. During myorelaxation and in supine position, the telescopic hardware can fix the neck in light hyperextension without the surgeon is aware of this and when the patient stands up and slightly flexes the neck on the chest, even in the presence of the collar, a failure of the construct can occur. A minimal asymmetry of the screws due to incorrect plate positioning can produce a "locus minoris resistentiae" (as probably in our case). The pull out of the expandable screws fatally produce the severe vertebral body damage we have experienced, leading the surgeon to more invasive procedures as the circumferential huge instrumentation and fusion. Sometimes, minimally invasive hardware with expandable screws (aimed to avoiding bicortical grip), with one piece plate and mesh with telescopic dynamics (aimed to spare time and to provide better stability of the construct) can produce undesired complications leading to much more invasive procedures. Abstract: Introduction: Multilevel cervical myelopathy without surgical treatment is generally poor in the neurological deficit without surgical decompression. The two main surgical strategies used for the treatment of multilevel cervical myelopathy are anterior decompression via anterior corpectomy or posterior decompression via laminctomy/laminoplasty. Presentation of case: We present the case of a 62 year-old lady, harboring rheumatoid artritis (RA) with gait disturbances, pain, and weakness in both arms. A C5 and C6 somatectomy, C4–C7 discectomy and, instrumentation and fusion with telescopic distractor "piston like", anterior plate and expandable screws were performed. Two days later the patient complained dysfagia, and a cervical X-ray showed hardware dislocation. So a C4 somatectomy, telescopic extension of the construct up to C3 with expandible screws was performed. After one week the patient complained again soft dysfagia. New cervical X-ray showed the pull out of the cranial screws (C3). So the third surgery "one stage combined" an anterior decompression with fusion along with posterior instrumentation, and fusion was performed. Discussion: There is a considerable controversy over which surgical approach will receive the best clinical outcome for the minimum cost in the compressive cervical myelopathy. However, the most important factors in patient selection for a particular procedure are the clinical symptoms and the radiographic alignment of the spine. the goals of surgery for cervical multilevel stenosis include the restoration of height, alignment, and stability. Conclusion: We stress the importance of a careful patients selection, and invocated still the importance for 360° cervical fixation.